Influence of digital finance service worth on customer satisfaction in Nepal - Shrestha, Binay; Agrawal, Neha (Journal of Commerce, Management, and Tourism Studies, 2023)
Customer satisfaction is a major factor to sustain competitive advantage in the present dynamic and competitive environment for the organisations. The present research work is conducted to find how customers of Nepalese banks are happy with online banking system. Primary data is collected through the questionnaire developed from SERVPERF model on 5-point Likert scale. A sample sizes of 335 total respondents taken as for data collection. The research is descriptive, causal comparative in nature. Variables included in the study are tangibles, reliability, assurance, responsiveness, empathy as exogenous variables and customer satisfaction with e-banking service quality as endogenous variable. The data analysis were performed through the techniques:- descriptive statistics, correlation, multiple regression.Results of the study showed  influenceof independent variables in all categories is positive and significant on dependent  with R2 value of 0.627 which means 62.7% change in endogenous variable is due to exogenous variables and rest 37.3% is due to the other factors outside the model. Study shows that customers of Nepal are appropriatelycontended with the digital banking system in Nepalese banks. Assurance have been found as highest determining factor for customer satisfaction in e-banking services in Nepal followed by reliability and empathy.